Right heart pulmonary circulation unit response to exercise in patients with controlled systemic arterial hypertension: insights from the RIGHT Heart International NETwork (RIGHT-NET) - Vriz, Olga; Palatini, Paolo; Rudski, Lawrence; Frumento, Paolo; Kasprzak, Jarosław D.; Ferrara, Francesco; Cocchia, Rosangela; Gargani, Luna; Wierzbowska-Drabik, Karina; Capone, Valentina; Ranieri, Brigida; Salzano, Andrea; et al. (Journal of Clinical Medicine, 2022)
Background. Systemic arterial hypertension (HTN) is the main risk factor for the development of heart failure with preserved ejection fraction (HFpEF). The aim of the study was was to assess the trends in PASP, E/E’ and TAPSE during exercise Doppler echocardiography (EDE) in hypertensive (HTN) patients vs. healthy subjects stratified by age. Methods. EDE was performed in 155 hypertensive patients and in 145 healthy subjects (mean age 62 ± 12.0 vs. 54 ± 14.9 years respectively, p < 0.0001). EDE was undertaken on a semi-recumbent cycle ergometer with load increasing by 25 watts every 2 min. Left ventricular (LV) and right ventricular (RV) dimensions, function and hemodynamics were evaluated. Results. Echo-Doppler parameters of LV and RV function were lower, both at rest and at peak exercise in hypertensives, while pulmonary hemodynamics were higher as compared to healthy subjects. The entire cohort was then divided into tertiles of age: at rest, no significant differences were recorded for each age group between hypertensives and normotensives except for E/E’ that was higher in hypertensives. At peak exercise, hypertensives had higher pulmonary artery systolic pressure (PASP) and E/E’ but lower tricuspid annular plane systolic excursion (TAPSE) as age increased, compared to normotensives. Differences in E/E’ and TAPSE between the 2 groups at peak exercise were explained by the interaction between HTN and age even after adjustment for baseline values (p < 0.001 for E/E’, p = 0.011 for TAPSE). At peak exercise, the oldest group of hypertensive patients had a mean E/E’ of 13.0, suggesting a significant increase in LV diastolic pressure combined with increased PASP. Conclusion. Age and HTN have a synergic negative effect on E/E’ and TAPSE at peak exercise in hypertensive subjects.
Gesehen am 26.09.2022